Perlindungan Hukum Masyarakat Kota Palangka Raya Akibat dari Pembakaran Hutan dan Lahan - Sanawiah Sanawiah (Anterior Jurnal, 2015)
The purpose of this study is to determine the cause of land and forest fire protection of the law and to find out on the community a result of land forest fire. The result of this research; paradigm human thinking today thought that nature and living environment is abundant treasures provided the optimal for the interests of human prosperity, so that nature with its entire contents and explored beyond the limits of exploitation and to disregard the maintened and the sustainability of the environment and destructive natural resources it self. As a result occurs in various environment damage resulting from forest fires and land has to the pont that very worrying. The absence of legal protection for the community resulting from forest fires and land and still loitering the incendiary land and forest.